ANTIBIOTIC PROPHYLACTICS ON CURETTAGE FOR PREVENTING PELVIC INFLAMMATORY DISEASE EVENTS: IS IT NECESSARY? - Herawati, Fauna; Rahem, Abdul; Handayani, Dwi; Yulia, Rika (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aimed to compare pelvic inflammatory disease (PID) symptoms in curettage procedure with three antibiotic prophylaxis strategies. Methods: The patients were allocated to three Groups (A, B, and C). Group A was patients receiving prophylactic antibiotics and post-curettage antibiotics, Group B received prophylactic antibiotics without post-curettage antibiotics, and Group C did not receive prophylactic antibiotics but received post-curettage antibiotics. The outcomes measured to identify the occurrence of PID symptoms included leukocytes, erythrocyte sedimentation rate, temperature, pain, vaginal discharge, and bleeding. Results: This study shows that there were no significant differences in any PID symptoms between antibiotic strategies except for pain scale (p=0.03). Conclusion: The PID symptoms between the three strategies of antibiotic prophylaxis were similar.